Cleft Lip and/or Palate and Auricular Malformations. (January 2015) - Suutarla, Samuli; Rautio, Jorma; Klockars, Tuomas
Objective: To study the relationship between cleft lip and/or palate and auricular malformations in Finnish patients with cleft. Design: Retrospective analysis of patients with an external ear malformation and either a cleft lip with or without a cleft palate (CL±P) or an isolated cleft palate (CP). Setting: Tertiary referral clinic. Patients: Review of hospital records of 100 patients from the register of 8200 patients with cleft in the Cleft and Craniofacial Centre at the Helsinki University Central Hospital. Main Outcome Measures: Proportions of variable auricular malformations among CL±P and CP patients. Results: Microtia is the most common auricular malformation among patients with cleft and is almost equally prevalent with both CL±P and CP. The prevalence of microtia increases as the severity of CL±P increases. The combination of microtia and CL±P or CP is frequently found with both oculo-auriculo-vertebral spectrum and Treacher Collins syndrome. Conclusions: Microtia seems to be the most common auricular malformation among patients with cleft. The prevalence of microtia seems to increase as the severity of CL±P increases, whereas in isolated CP microtia seems to occur independently.